Comprehensive review of the duplication 3q syndrome and report of a patient with Currarino syndrome and de novo duplication 3q26.32‐q27.2. Issue 5 (10th October 2016) - Dworschak, G.C.; Crétolle, C.; Hilger, A.; Engels, H.; Korsch, E.; Reutter, H.; Ludwig, M.
Abstract : Partial duplications of the long arm of chromosome 3, dup(3q), are a rare but well‐described condition, sharing features of Cornelia de Lange syndrome. Around two thirds of cases are derived from unbalanced translocations, whereas pure dup(3q) have rarely been reported. Here, we provide an extensive review of the literature on dup(3q). This search revealed several patients with caudal malformations and anomalies, suggesting that caudal malformations or anomalies represent an inherent phenotypic feature of dup(3q). In this context, we report a patient with a pure de novo duplication 3q26.32‐q27.2. The patient had the clinical diagnosis of Currarino syndrome (CS) (characterized by the triad of sacral anomalies, anorectal malformations and a presacral mass) and additional features, frequently detected in patients with a dup(3q). Mutations within the MNX1 gene were found to be causative in CS but no MNX1 mutation could be detected in our patient. Our comprehensive search for candidate genes located in the critical region of the duplication 3q syndrome, 3q26.3‐q27, revealed a so far neglected phenotypic overlap of dup(3q) and the Pierpont syndrome, associated with a mutation of the TBL1XR1 gene on 3q26.32. Abstract :